Lower Cretaceous non-marine ostracods of the Orós Formation, Iguatu basin: Taxonomy and biostratigraphic considerations. (February 2021) - Batista dos Santos Filho, Marcos Antonio; Fauth, Gerson; Sames, Benjamin
Abstract: Non-marine ostracods have been used for a long time to aid in the understanding of the Lower Cretaceous sedimentary deposits of Brazil, with various studies showing their value for biostratigraphic zonation in different basins. The northeastern region of Brazil contains several basins south of the Potiguar Basin which originated from the rifting that resulted from the opening of the Atlantic Ocean, and thus contain an important record of the Cretaceous Period. This paper has the objective of studying the ostracods recovered from two adjacent sections (Transnordestina A and Transnordestina B) belonging to the Orós Formation, Iguatu Basin, Ceará, Brazil, detailing their taxonomy and developing biostratigraphic inferences based on the observed fauna. A total of 19 species were found in the analyzed samples, distributed among 11 genera and five families: Cypridea hystricoides, Cypridea paraibensis, Cypridea cf . C. clavata, Cypridea punctacentralis sp. nov., Brasacypris ovum, Pattersoncypris sinuata, Pattersoncypris cf . P. sinuata, Pattersoncypris ? sp., Ilyocypris ? arca sp. nov., Ilyocypris ? latanodi sp. nov., Rhinocypris ? ericius sp. nov., Pythagoracypris latavectis gen. et sp. nov., Hastacypris adamantem gen. et sp. nov., Looneyellopsis mvili, Musacchiocythere plastica, Musacchiocythere ? sp., Alicenula leguminella, Alicenula cf. D. oblonga, and an incertae sedis species. From the recovered species, a Hauterivian–Aptian interval can be inferred for the studied sections. Highlights: First extensive ostracod taxonomic study of the Iguatu Basin, Ceará state, Brazil. Abundant and diverse material: over 17, 000 recovered specimens, 19 different species from 11 genera and 5 families. Six new species and two new genera of non-marine ostracods are described. Hauterivian–Aptian age inferred for section, possible stratigraphic range change for Brasacypris ovum, Pattersoncypris .